Etnobotani Tanaman Obat Tradisional Pasca Melahirkan di Kecamatan Singkil Utara Kabupaten Aceh Singkil - Alfiani, Anggun Desrah; Kamaliah, Kamaliah; Sardi, Arif (KENANGA : Journal of Biological Sciences and Applied Biology, 2026)
Ethnobotany of medicinal plants is the study of cultural interactions between humans and medicinal plants, documenting traditional healthcare knowledge based on local wisdom and cultural practices passed down through generations. The postpartum period causes various physiological and physical changes in mothers, such as widening of the hips, the appearance of abdominal stretch marks, swelling of the legs, varicose veins, and weight gain. Communities in North Singkil Subdistrict, Aceh Singkil Regency, continue to utilize traditional medicinal plants for postpartum care as part of their local wisdom. This makes the area relevant as a research site to explore its ethnobotanical potential and to understand the role of tradition in maintaining community health, especially amid the growing tendency in some regions to abandon traditional medicine.This study aimed to identify the types of medicinal plants used and to describe their methods of preparation and application in postpartum care. The study employed a purposive sampling method involving 35 informants selected through interview techniques, and the collected data were analyzed descriptively. The results showed that the community utilizes 32 plant species belonging to 20 families as traditional postpartum remedies, with the Zingiberaceae family being the most dominantly used group. These plants are applied through two primary methods: topical application (rubbing ointment/lampok) and oral consumption. Preparation for oral use involves either boiling or direct consumption without processing (raw). Keywords: ethnobotany; medicinal plants; postpartum.